Implementasi Kebijakan Pakaian Seragam Sekolah bagi Peserta Didik Jenjang Pendidikan Dasar di Kota Pekanbaru - Sella Safira Deandra; Zulkarnaini Zulkarnaini (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The school uniform policy is part of the broader education policy aimed at instilling the values of nationalism, social equality, discipline, and fostering a spirit of unity among students. However, in its implementation in Pekanbaru City various issues are still found, such as the financial burden placed on parents for purchasing uniforms, lack of transparency from schools, and suboptimal parental involvement and supervision by the education office. This study employs a qualitative method with a descriptive phenomenology approach. The research refers to the policy implementation theory of Yulianto Kadji, namely the MSN Approach (Mentality-Approach, System-Approach, and Networking-Approach). Data were collected through in-depth interviews, direct observation, and documentation. Informants included representatives from the Pekanbaru City Education Office, school principals, and parents. The results of the study indicate that the implementation of the school uniform policy in Pekanbaru City has not been optimal. From the mentality approach, there are still objections from parents regarding the cost of uniforms and limited understanding of the policy regulations. From the systems perspective, regulations are not consistently enforced by schools, including a lack of prioritization for underprivileged students and the absence of strict sanctions for policy violations. Meanwhile, from the networking approach, parental involvement and the role of school committees in decision-making remain weak, resulting in the lack of effective strategic partnerships between schools, parents, and the education office.